Semisynthetic flavonoid 7-O-galloylquercetin activates Nrf2 and induces Nrf2-dependent gene expression in RAW264.7 and Hepa1c1c7 cells - Roubalová, Lenka; Biedermann, David; Papoušková, Barbora; Vacek, Jan; Kuzma, Marek; Křen, Vladimír; Ulrichová, Jitka; Dinkova-Kostova, Albena T; Vrba, Jiří (Chemico-biological interactions, 2016)
The natural flavonoid quercetin is known to activate the transcription factor Nrf2, which regulates the expression of cytoprotective enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1). In this study, a novel semisynthetic flavonoid 7-O-galloylquercetin (or quercetin-7-gallate, 3) was prepared by direct galloylation of quercetin, and its effect on the Nrf2 pathway was examined. A luciferase reporter assay showed that 7-O-galloylquercetin, like quercetin, significantly activated transcription via the antioxidant response element in a stably transfected human AREc32 reporter cell line. In addition, 7-O-galloylquercetin caused the accumulation of Nrf2 and induced the expression of HO-1 at both the mRNA and protein levels in murine macrophage RAW264.7 cells. The induction of HO-1 by 7-O-galloylquercetin was significantly suppressed by N-acetyl-l-cysteine and SB203580, indicating the involvement of reactive oxygen species and p38 mitogen-activated protein kinase activity, respectively. HPLC/MS analyses also showed that 7-O-galloylquercetin was not degalloylated to quercetin, but it was conjugated with glucuronic acid and/or methylated in RAW264.7 cells. Furthermore, 7-O-galloylquercetin was found to increase the protein levels of Nrf2 and HO-1, and also the activity of NQO1 in murine hepatoma Hepa1c1c7 cells. Taken together, we conclude that 7-O-galloylquercetin increases Nrf2 activity and induces Nrf2-dependent gene expression in RAW264.7 and Hepa1c1c7 cells.
Keywords: Cell Survival; hemoxygenasa-1; reaktivní formy kyslíku; NAD(P)H Dehydrogenase (Quinone); Biotransformation; Humans; inhibitory proteinkinas; Metabolome; regulace genové exprese; NF-E2-Related Factor 2; quercetin; lidé; p38 Mitogen-Activated Protein Kinases; zvířata; reportérové geny; myši; Quercetin; Reactive Oxygen Species; Mice; mitogenem aktivované proteinkinasy p38; RAW 264.7 buňky; metabolom; Protein Kinase Inhibitors; enzymová indukce; Gene Expression Regulation; Genes, Reporter; Heme Oxygenase-1; nádorové buněčné linie; faktor 2 související s NF-E2; biotransformace; Animals; Cell Line, Tumor; RAW 264.7 Cells; hmotnostní spektrometrie; viabilita buněk; Enzyme Induction; Mass Spectrometry; NAD(P)H dehydrogenasa (chinon)